Letter from W. E. Du Bois of the United States Mint to James Curtis Booth - Du Bois, William E. (William Ewing) (1841)
Note to James Curtis Booth (1810-1888) from William Ewing Du Bois (1810-1881), Assistant Assayer of the United States Mint, thanking Booth for his specimens.
Keywords: Mint of the United States; Booth, James Curtis, 1810-1888; Du Bois, William E. (William Ewing), 1810-1881; United States Mint; Coins